SAT0476 COMPLIANCE AND PERSISTENCE OF ANTI-OSTEOPOROTIC TREATMENTS IN PATIENTS WITH HIP FRACTURE. (2nd June 2020) - Paredes, S.; Guinovart, M.; Basco, A.; Llop, C.
Abstract : Background: Osteoporotic fractures have a high health and economic impact. The best strategy to minimize the incidence of fractures is, certainly, the prevention of these that includes pharmacological treatments. However, long-term discontinuation treatment and sub-optimal compliance of the treatment are common. Objectives: The aim of the study is to quantify the therapeutic compliance and permanence of the osteoporosis pharmacological treatments for patients who were discharged from hospitals in Catalonia with hip fracture during 2017. Methods: From the Hospital Discharge Database of the Catalan Health Service, all patients who had been discharged during 2017 were selected with the main diagnosis of femur fracture, according to the coding CIM-9. The consumption of drugs to assess compliance and permanence was obtained from the Catalan Health Service pharmacy Database. The study period was 18 months from the date of hospital discharge. Patients who died, moved to other areas or switched their treatment were excluded from the study. Good compliance was considered when sufficient drug was obtained to cover 80% of the time since treatment was prescribed until the end of the study period. In the case of denosumab, good post-fracture compliance was considered when the treatment time was remained at least 12 months. Permanence was considered positive if a drug had been obtained during the last three months of the study period. To compare the differences in compliance and permanence between the patients treated with different drugs, the chi-square statistic was used, considering statistically significant differences if p<0.05. Results: 8, 354 patients were discharged with the main diagnosis of hip fracture. Of these, 1, 712 patients (20.49%) were treated after been discharged. After applying the exclusion criteria, the final sample was made up of 1, 327 patients. 81, 54% were women, and the median age was 84, 79 years. The most commonly used treatments were bisphosphonates (69%), denosumab (23%) and teriparatide (7%) The results of good compliance and permanence of treatment were those described in the table. Conclusion: The results obtained suggest that a small number of patients were treated after a hip fracture (20.49%) in addition the instituted treatments are followed in a suboptimal way. It is necessary to investigate which factors may lead to the detection of potential non-compliant patients. It seems appropriate to consider drugs that facilitate compliance and permanence of treatment. Our results suggest that denosumab and teriparatide improve compliance compared with oral bisphosphonates. The introduction of specific plans and cross-sectional health structures between levels of care should lead to improve detection, treatment and compliance in patients with osteoporosis. Disclosure of Interests: SILVIA PAREDES Consultant of: Amgen, Lilly, Ferrer, Roche, Novartis; BMS, Maria Guinovart: None declared, Aida Basco: None declared, Carles Llop: None declared